Pengaruh Live Streaming dan Promo Free Shipping Terhadap Impulse Buying Produk Somethinc pada Aplikasi Shopee : Studi pada Mahasiswa Fakultan Ekonomi dan Bisnis Universitas Negeri Makasar - Nurul Aszizah Adelia Putri Nur; Anwar Ramli; Ilma Wulansari Hasdiansa; Siti Hasbiah; Isma Azis Riu (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This study was conducted to analyze the influence of the live streaming feature and free shipping promo on impulse buying behavior for Somethinc brand beauty products on the Shopee e-commerce platform. The background of this study is based on the increasing competition in digital businesses, especially in the beauty industry, which encourages business actors to utilize creative marketing strategies to attract consumers' attention. The live streaming feature is present as an interactive media that allows sellers to communicate directly with buyers, show product authenticity, and create a more personalized shopping experience. Meanwhile, the free shipping promo is considered one of the most effective marketing strategies to encourage spontaneous purchasing decisions, because it can reduce the burden of additional costs that are usually a consumer consideration. The research method used is quantitative with a descriptive approach. The research sample consisted of 100 students of the Faculty of Economics and Business, Makassar State University who had purchased Somethinc products through Shopee. Data collection was carried out using a structured questionnaire, then analyzed using multiple linear regression techniques to determine the effect of independent variables on the dependent variable. The results showed that both live streaming and the free shipping promo have a positive and significant influence on impulse buying. Live streaming can foster a sense of spontaneous buying desire because of its attractive, informative, and persuasive nature. On the other hand, the free shipping promotion is a powerful incentive for consumers to shop without much consideration. Simultaneously, these two factors contribute to increased consumer interest in Somethinc products on Shopee. This finding provides important implications for e-commerce and the beauty industry to further optimize digital marketing strategies based on interactivity and cost incentives to increase consumer impulse purchases.